Marathon specialization in elites: A head start for Africans - Noble, T. J.; Chapman, R. F. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To assess differences in event-specific specialization between elite African and non-African male marathon runners based on age, performance, and career length. Methods: The top 90 African marathoners from 2001 to 2015 were compared with the top 90 non-African marathoners from the same time period across various markers related to specialization age, performance, and career length. Independent t tests were used to identify significant differences (P<.05) between the African and non-African groups. Linear regression was used to explore the relationship between first half-marathon and best full-marathon performance. A 1-way ANOVA and Bonferroni correction was used to assess differences in specialization age and rates of performance improvement and decline. Results: African marathoners were found to specialize, reach peak levels of performance, and retire at younger ages than non-African marathoners (P<.001). In addition, African marathoners were found to be faster at these same career time points and in half-marathon performance (P<.001). There was no significant difference in the number of career marathons run between groups, but African marathoners were found to race more frequently than non-African marathoners (P<.001). Half-marathon performance was positively correlated with marathon performance (r2=.67). Marathon athletes who specialized at early ages experienced significantly higher rates of improvement than those who specialized at older ages. (P<.05). Conclusions: The findings suggest that elite African marathoners achieve a greater level of performance at younger ages than their non-African counterparts. Furthermore, current marathon talent-identification practice may benefit from using half-marathon performance.